Analisis Instrumen Penilaian Berbasis Higher Order Thinking Skills pada Mata Kuliah Matematika Lanjut - Sari Saraswati; Iesyah Rodliyah; Novia Dwi Rahmawati (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2021)
This study aims to determine the quality of the assessment instrument based on Higher Order Thinking Skills (HOTS) based on qualitative and quantitative analysis. The type of research is descriptive quantitative. This study involved 32 Mathematics Education students. The research instrument was in the form of a question review sheet and 16 multiple-choice items based on HOTS based on Bloom's taxonomy. The qualitative study covers aspects of content/material, construction, and language. While the quantitative analysis is based on the Classical Test Theory approach with the help of the ANATES version 4.0.9 program. Aspects that are analyzed quantitatively include validity, reliability, level of difficulty, discriminatory power, and distractor functions. The results showed that 1) the instrument reached the valid criteria from the results of qualitative and quantitative studies, 2) the reliability of the items reached 0.87 including very high criteria, 3) the discriminatory power of at least 22.22%, 4) the level of difficulty of the questions included 25% easy, 31.25% moderate, while 43.75% difficult, and 5) all distractors work well. This HOTS-based assessment instrument can be applied as an evaluation tool in familiarizing students with higher-order thinking.